Environmental & architectural phenomenology. Vol. 1, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 1990)
Vol. 1, No. 1, Winter 1990 (includes noteworthy publications, conference report of 1989 SPEP & SPHS Meetings, and reflections by Margaret Boschetti's students).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals